DRUG THERAPY IN THE PROGRESSED CML PATIENT WITH MULTI-TKI FAILURE - Ibrahim C. Haznedaroglu (Mediterranean Journal of Hematology and Infectious Diseases)
The aim of this paper is to outline pharmacotherapy of the ‘third-line management of CML’ (progressive disease course after sequential TKI drugs. Current management of CML with multi-TKI failure is reviewed. TKI (bosutinib, ponatinib, dasatinib, nilotinib) and non-TKI (omacetaxine mepussecinate, IFN or PEG-IFN) drugs are available. The literature search was made in PubMed with particular focus on the clinical trials, recommendations, guidelines and expert opinions, as well as international recommendations. Progressing CML disease with multi-TKI failure should be treated with alloSCT based on the availability of the donor and EBMT transplant risk scores. The TKI and non-TKI drugs shall be used to get best promising (hematological, cytogenetic, molecular) response. During the CP-CML phase of multi-TKI failure, 2nd generation TKIs (nilotinib or dasatinib) are used if they remained. Bosutinib and ponatinib (3rd generation TKIs) can be administered in triple-TKI failed (imatinib and nilotinib and dasatinib) patients. The presence of T315I mutation at any phase requires ponatinib or omacetaxine mepussecinate therapy before allografting. During the AP/BC-CML phase of multi-TKI failure, the most powerful TKI available (ponatinib or dasatinib if remained) together with chemotherapy should be given before alloSCT. Monitoring of CML disease and drug off-target risks (particularly vascular thrombotic events) are vital.